Peningkatan Keterampilan Komunikasi Mahasiswa Calon Guru Melalui Kegiatan Analisis Artikel Ilmiah Dari Jurnal Nasional - Hikmawati Hikmawati; Haerunisyah Sahidu; Syahrial Ayub; Kosim Kosim (Pascasarjana Universitas Mataram, 2021)
The purpose of this service activity is to improve the communication skills of prospective teacher students through the analysis of scientific articles from national journals in Indonesia. This activity was carried out online from March to May 2021 as many as 12 meetings. Participants of this activity were 27 student teacher candidates from a university in the city of Mataram. The method of implementing this activity is: Students are given an explanation of the material at each meeting via the google meet platform. Students are given the opportunity to ask questions verbally. Students are assigned to search for scientific articles from national journals according to the topics discussed, this activity is carried out through google search. Students download scientific article files from national journals, then upload the file through the